TBI-induced nociceptive sensitization is regulated by histone acetylation. (June 2017) - Liang, De-Yong; Sahbaie, Peyman; Sun, Yuan; Irvine, Karen-Amanda; Shi, Xiaoyou; Meidahl, Anders; Liu, Peng; Guo, Tian-Zhi; Yeomans, David C.; Clark, J. David
Abstract: Chronic pain after traumatic brain injury (TBI) is very common, but the mechanisms linking TBI to pain and the pain-related interactions of TBI with peripheral injuries are poorly understood. In these studies we pursued the hypothesis that TBI pain sensitization is associated with histone acetylation in the rat lateral fluid percussion model. Some animals received hindpaw incisions in addition to TBI to mimic polytrauma. Neuropathological analysis of brain tissue from sham and TBI animals revealed evidence of bleeding, breakdown of the blood brain barrier, in the cortex, hippocampus, thalamus and other structures related to pain signal processing. Mechanical allodynia was measured in these animals for up to eight weeks post-injury. Inhibitors of histone acetyltransferase (HAT) and histone deacetylase (HDAC) were used to probe the role of histone acetylation in such pain processing. We followed serum markers including glial fibrillary acidic protein (GFAP), neuron-specific enolase 2 (NSE) myelin basic protein (MBP) and S100β to gauge TBI injury severity. Our results showed that TBI caused mechanical allodynia in the hindpaws of the rats lasting several weeks. Hindpaws contralateral to TBI showed more rapid and profound sensitization than ipsilateral hindpaws. The inhibition of HAT using curcumin 50 mg/kg s.c reduced mechanical sensitization while the HDAC inhibitor suberoylanilide hydroxamic acid 50 mg/kg i.p. prolonged sensitization in the TBI rats. Immunohistochemical analyses of spinal cord tissue localized changes in the level of acetylation of the H3K9 histone mark to dorsal horn neurons. Taken together, these findings demonstrate that TBI induces sustained nociceptive sensitization, and changes in spinal neuronal histone proteins may play an important role. Highlights: Pain after traumatic brain injury (TBI) is common and often persistent. Using the rat lateral fluid percussion model, it was observed that hindpaw allodynia is present for three weeks after TBI. Damage to pain processing areas of the brain can be demonstrated after TBI. Agents regulating the epigenetic acetylation of histone proteins modified the time course of TBI-induced allodynia.